The Post-Modification of Noun Phrase: Types and Distributions on Abstracts of Local and International Journals - Shanty A.Y.P.S Duwila (Universitas Airlangga, 2020)
Focusing on single and multiple post-modification of noun phrase complexity in academic writing, this study adopted Berlage’s (2014) types of single and multiple post-modification of noun phrase to investigate the types and distributionof noun phrase on 15 abstracts of accredited local journal and 15 international journal indexed by Scopus. Subjects, objects, and complements are coded manually and then extracted for noun phrases. The findings revealed that both groups of writers heavily relied on noun phrase involving prepositional phrase in single-post modification and noun phrase involving prepositional phrase(s) and coordination(s) in multiple-post modification. This finding may give contribution to EFL teachers and material developers in order to provide information and materials about NP post modifiers that can be used in academic writing.